Keefektifan Video Pembelajaran Berbantu Kinemaster pada Tema 7 Subtema 1 Terhadap Hasil Belajar Peserta Didik SD N 02 Banjarsari - Tikhkamatul Khasanah; Fine Reffiane; Qoriati Mushafanah (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study was to determine whether or not the kinemaster-assisted learning video on the theme of 7 events in the life of subtheme 1 was effective on the learning outcomes of fifth grade students. This type of research is a quantitative study using experimental methods with a research design of One Group Pre-Test Post-Test Design. The population in this study were all fifth grade students of SD N 02 Banjarsari. using a non-probability sampling technique with saturated sampling type. Data collection techniques in this study were obtained through observation, interviews, tests and documentation. From the pretest value, it shows that the average value is 52.85 while the posttest value shows that the average value is 87.14 and based on the t-test analysis, it is obtained that tcount is 19.4210 with t table of 2.052. It can be concluded that arithmetic> ttable, meaning Ho is rejected. The analysis of completeness of learning before being treated is 14%, while after being given treatment is 93%. Thus, it can be concluded that the kinemaster-assisted learning video is overall effective on student learning outcomes.